2021
DOI: 10.1101/2021.06.30.21259766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adherence to the EAT-Lancet Healthy Reference Diet in relation to Coronary Heart Disease, All-Cause Mortality Risk and Environmental Impact: Results from the EPIC-NL Cohort

Abstract: Objectives: To construct a diet-score measuring the level of adherence to the Healthy Reference Diet (HRD), to explore whether adherence to the HRD is associated with coronary heart disease (CHD), all-cause mortality risk, and to calculate its environmental impact. Design: Prospective cohort study. Setting: The Dutch contribution to the European Prospective Investigation into Cancer and Nutrition (EPIC-NL). Participants: 37,349 adults (20-70y) without CHD at baseline. Main outcome measures: Primary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…We found that higher PHD-S was associated with lower GHG emissions, which was in line with other studies . This association was largely driven by lower consumption of total grains (mostly refined grains) and red meat, and was consistent with the findings that rice, as the main crop on a global scale, emits more GHG than other crops, and shifting to a diet free of animal products (especially red meat) could reduce GHG emissions by 49% .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that higher PHD-S was associated with lower GHG emissions, which was in line with other studies . This association was largely driven by lower consumption of total grains (mostly refined grains) and red meat, and was consistent with the findings that rice, as the main crop on a global scale, emits more GHG than other crops, and shifting to a diet free of animal products (especially red meat) could reduce GHG emissions by 49% .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these studies were conducted only in Western populations, without considering each individual’s energy intake and different levels of adherence to PHD . To date, only a few studies using individualized data have linked PHD to both environmental impacts and mortality outcomes . Laine et al revealed that higher adherence to PHD was associated with lower GHG emissions, land use, and mortality risk among Europeans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be relevant to study them to confirm or infirm this association in our study population. However, a Dutch study, which included 2,543 cases, reported a 15% reduction in coronary heart disease risk with a higher adherence to EAT-Lancet recommendations (60). Metaanalyses on the MEDI-Lite (62,63), also reported negative associations between diet quality scores and risk of all CVD while it was not the case in our study, nor in the Lazarova's study, which also did not find an association between adherence to the EAT-Lancet diet and the occurrence of all-cause stroke (64).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CVD, the relationships between stroke, some subtypes both ischemic and hemorrhagic, and the EAT-Lancet recommendations have been studied (28,59), however to our knowledge, only one study on coronary diseases has been conducted (60). Whether carried out in the elderly or in the general population, no association was found between a better adherence to the EAT-Lancet recommendations and the risk of stroke (28,59).…”
Section: Discussionmentioning
confidence: 99%